Динаміка привідних систем і стрілових конструкцій стрічкових конвеєрів мобільних машин - Поліщук, Леонід Клавдійович (Вінницький національний технічний університет, 2017)
Дисертація присвячена розв’язанню актуальної наукової проблеми підвищення ефективності функціонування привідних систем і стрілових конструкцій стрічкових конвеєрів мобільних машин за рахунок усунення резонансних явищ, а також зниження динамічних зусиль у пружних ланках шляхом застосування вмонтованого гідроприводу, оснащеного основним і додатковим моторами та системою керування. Побудовано нелінійні математичні моделі і проведено дослідження динамічних явищ у приводі та у вітках конвеєра. Обґрунтовано параметри системи керування, які забезпечують стійку роботу конвеєра в умовах значних коливань експлуатаційних навантажень. Розроблено метод розрахунку перехідних процесів у стрічкових конвеєрах з урахуванням рухомості меж довгомірних віток транспортувального органу, що дало можливість значно підвищити точність визначення зусиль у стрічці. Із застосуванням матричного методу початкових параметрів проведено математичне моделювання вільних і вимушених коливань багатопрогонових стрілових конструкцій з жорстким та шарнірним сполученнями секцій. Досліджено вплив нерівномірності розподілу вантажу та інших експлуатаційних характеристик конвеєра на навантаження елементів приводу і стрілової конструкції. Вивчено сумісний вплив змінних зусиль у несівній конструкції і характеристик робочого середовища на довговічність та залишковий ресурс елементів стріли. Диссертация посвящена решению актуальной научной проблемы повышения эффективности функционирования приводных систем и стреловых конструкций ленточных конвейеров мобильных машин за счет устранения резонансных явлений, а также снижения динамических усилий в упругих звеньях путем применения встроенного гидропривода, оснащенного основным и дополнительным моторами и системой управления. Построено нелинейные математические модели и проведены исследования динамических явлений в приводе и в ветвях конвейера. Обоснованно параметры системы управления, обеспечивающих устойчивую работу конвейера в условиях значительных колебаний эксплуатационных нагрузок. Разработан метод расчета переходных процессов в ленточных конвейерах с учетом подвижности границ длинномерных веток транспортирующего органа, что позволило значительно повысить точность определения усилий в ленте. С применением матричного метода начальных параметров проведено математическое моделирование свободных и вынужденных колебаний многопролетных стреловых конструкций с жестким и шарнирным соединениями секций. Исследовано влияние неравномерности распределения груза и других эксплуатационных характеристик конвейера на нагрузку элементов привода и стреловой конструкции. Изучено совместное влияние переменных усилий в несущей конструкции и характеристик рабочей среды на долговечность и остаточный ресурс элементов стрелы. The dissertation is focused on the solution of a current scientific problem: improvement of operation efficiency of drive systems and boom structures of mobile machinery belt-conveyers resulting from elimination of resonance phenomena and decrease of dynamic forces on elastic elements through application of a built-in drive equipped with main and auxiliary motors and a control system. Scientific fundamentals of the development of built-in hydraulic drives sensitive to load variations have been developed using non-linear mathematical models. The advantages of using built-in hydraulic drives with hydraulic instrumentation in drive system have been proven. Methods of analyzing non-stationary operation modes of a belt conveyer hydraulic drive unit with main and auxiliary hydraulic motors and device or control system, sensitive to load variations, have been developed. Through the comparison of theoretical and experimental values of dynamic characteristics of a hydraulic drive with control device, we have determined the deviations of basic parameters of theoretical determination such as rotational stiffness of the system, inertial load, volume of pump line and character of load variations within the limit of 8,9% to 17,2%. This proves the validity of assumptions made in the process of theoretical research and the mathematical model of the drive may be considered indicative of the real hydraulic mechanical system. Parameters of the hydraulic drive with control system and transporting part of the conveyer have been determined, the change of these parameters causes the change of transient process time by the pressure in pump line at the phase of additional hydraulic motor vary from 0.11 sec. to 0.15 sec., at the phase of combined operation of hydraulic motors---from 0.05 sec. to 0.12 sec., at the phase of load decrease and additional hydraulic motor cut off--from 0.9 sec. to 0.17 sec. and expressed as percentages --- from 15% to 45%, from 4% to 12%, from 20% to 55%, respectively. Mathematical models of start-up device dynamic processes have been constructed, with device operation synthesized on the basis of a rational method of belt conveyer startup and hydraulic drive control with parallel hydraulic motors, accounting for useful resistance force variations and hydrodynamic phenomena in the drive. Conditions for efficient usage of drive control systems have been determined. According to these conditions, the pressure space of additional hydraulic motor qм2 must not exceed 75% of this parameter qм2 value of the main hydraulic motor, the ratio of hermetic sealing areas of lock element of the sensor is the value -f1/f2=0.7. The research recommends measures aimed at construction changes in control system elements to avoid negative phenomena in control system operation. A method of transient processes calculation in belt conveyers has been developed that accounts for the mobility limits of long elastic links, applying the developed algorithm of transient and steady state modes calculation in mechanical system of the conveyer. Mathematical models of free and harmonic forced vibrations of boom constructions in the form of continuous multispan or disembodied articulated stiff and flexible beams have been developed on the basis of the bending theory or Timoshenko’s non-classic beam theory. Natural frequencies of such constructions have been determined to depend on the mass of the transported load and on the rigidity of retaining ropes and can change, depending on technical characteristics of the ropes and operation conditions of the spreader, in a broad range. Research of dynamic processes of forced vibrations has shown that the character of transported load distribution along the boom greatly influences the amplitude and frequency of boom dynamic loads. Both natural frequencies and amplitudes of forced vibrations of a boom mechanical system depend on geometric and flexible inertial characteristics of carrying construction. In addition, the characteristic of forced vibrations of the boom is influenced by load mass, non-uniformity of its distribution along the length of the belt and speed of load motion. The impact of loading mode and conditions of long-term operation of carrying construction of the boom on mechanical properties of the material has been studied. Long operation of the boom resulted in considerable reduction of impact elasticity of the metal at minor increase of strength characteristic and drop of ductility. Applying analytical relations for CLI (coefficient of load intensity) characteristic values of cracking-like faults lengths have been calculated. These faults could be considered with a high probability as precursors of structure destruction. Practical recommendations have been developed regarding the assessment of boom construction durability with modeled crack-like faults of different form and geometry by means of determination of limiting value of loading cycles. Application of criterial assessment in the process of circuit search of drives constructions and their structural-functional elements enabled development of built-in drives with improved technical–economic characteristics. Calculation of technical-economic indices, characterizing the efficiency of the replacement of the equipment, installed at Private Joint –Stock Company “Strizhivka Quarry” by the new equipment, developed on the base of built-in drive, proves the expediency of such measure. In this case, the volume of the processed granite mass increases (by 7.4%), capital and operation expenses decrease (by 60%), production cost decreases (by 4.2%), net profit increases (by 7.3%). Additionally, gross profit increases (by 12.0%), profitability index grows (by 10.7%), and payback period decreases (by 18.8%).
Динамика приводных систем и стреловых конструкций ленточных конвейеров мобильных машин
Dynamics of drive systems and boom construction of belt conveyers on mobile machinery
Keywords: динамічні процеси; математичне моделювання; гідропривід; пристрій та система керування; змінні навантаження; стрілова конструкція; механічні коливання; ресурс; динамические процессы; математическое моделирование; гидропривод; устройство и система управления; переменные нагрузки; стреловая конструкция; механические колебания; ресурс; dynamic processes; mathematical modeling; hydraulic drive; control device and control system; variable loads; boom construction; mechanical vibrations; resource